(untitled) (AUN INTERNATIONAL CONFERENCE, 2025)
This paper is an assessment of the roles of endogenous conflict resolution strategy in promoting social justice and peace in Nigeria. This paper focuses attention on the relevance of Endogenous conflict resolution in addressing crisis in Nigeria. The paper discusses the conceptual meaning of Endogenous conflict resolution. It examines the various strategies and approaches in Endogenous conflict resolution to address the incessant societal conflicts in human societies. In addition, the paper discusses the efficacy of endogenous conflict resolution. The paper therefore adopted the structural conflict theory as its theoretical framework to provide theoretical orientation to the discourse. The paper derives its materials from selected books and internet materials. The paper highlighted the importance of Endogenous conflict resolution. The paper concludes that Endogenous conflict resolution should be adopted as an alternative strategy in addressing the several societal conflicts.